Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm looking for some help with this probability problem.

Here's the question:

Suppose that $X$ and $Y$ are independent standard normal random variables. Show that the probability density function of $Z = X / |Y|$ is given by $$ f(t) = \frac{1}{\pi(1+t^2)}, \quad (-\infty < t < \infty). $$

Thanks for looking through my question.

-updated- Hi guys, I've looked through the solution and am still thinking, i'm also thinking if its possible to log the expressions and apply convolution theorem... thanks for the answers once again.

-updated- tried the solution using first method but couldn't figured out how to complete the last step.

Heres how i did it:

$f(x,y) = f_{x}(x)f_{y}(y) = \frac{1}{2\pi}e^{-\frac{1}{2}(x^2 + y^2)}$

let Z = X/|Y|, V = X then x = v, y = v/z

the Jacobian J = $x_{z}y_{v}-x_{v}y_{z} = \frac{v}{z^2}$

by Transformation theorem,

$w(z,v)=f(v,\frac{v}{z})|J| = ???$

Will someone please point out to me how do i proceed from here to obtain f(t)? thanks a lot!

-update 3- this is actually a Cauchy density!! thanks guys, i think i got it figured out.

share|improve this question
1  
Take $\varphi$ a continuous function with compact support, and compute $E\left[\varphi\left(\frac X{|Y|}\right)\right]$ using the fact that you know a probability density of $(X,Y)$. –  Davide Giraudo Nov 6 '11 at 19:16
    
Please see responses to this question which addresses your particular question as an example. –  Sasha Nov 6 '11 at 20:00
    
Like @Davide said. Try to emulate this. –  Did Nov 6 '11 at 20:41
    
@Sasha, about your answer to the other question, note that a crucial hypothesis missing there is available here. –  Did Nov 6 '11 at 20:45

3 Answers 3

up vote 0 down vote accepted

I imagine you could use the following theorem:


Let $X_1$ and $X_2$ be jointly continuous r.v.'s with joint density $f_{X_1,X_2}$. Let $Y_1=g(X_1,X_2)$ and $Y_2=g_2(X_1,X_2)$.

If

1) $y_1=g(x_1,x_2)$ and $y_2=g_2(x_1,x_2)$ can be uniquely solved for $x_1$ and $x_2$ by, say, $x_1=h_1(y_1,y_2)$ and $x_2=h_2(y_1,y_2)$

and

2) $g_1$ and $g_2$ have continuous partials with $$ J(x_1,x_2) ={\partial g_1\over\partial x_1}{\partial g_2\over\partial x_2} - {\partial g_1\over\partial x_2}{\partial g_2\over\partial x_1} \ne0, $$ then

$$ f_{Y_1,Y_2}(y_1,y_2) = f_{X_1,X_2} (x_1,x_2) |J(x_1,x_2)|^{-1}, $$ where

and $x_1=h_1(y_1,y_2)$ and $x_2=h_2(y_1,y_2)$.


Use the above to find the joint distribution of $Y_1=X$ and $Y_2=X/Y$ (with $X_1=X$ and $X_2=Y$); then integrate to obtain the distribution of $Y_2$.

This, by the way, is a problem in Sheldon Ross' ``A first Course in Probability'' (Chapter 6, Theoretical Exercise 33.)

Edit: This may be a ``sledgehammer''. Refer to the post suggested by Sasha...

share|improve this answer

One way is polar coordinates: $(X,Y)= R(\cos \Theta,\sin\Theta)$. Observe that $X/Y=\cos\Theta/\sin\Theta$. Find the distribution of $(\cos \Theta,\sin\Theta)$ by thinking about the density of $(X,Y)$. You'll see that that's easy and the answer you get is simple. Then think about tangents and cotangents.

share|improve this answer
1  
Also, this works whenever the joint density of $X$ and $Y$ is rotationally symmetric around the origin. (If $X$ and $Y$ are independent, though, then that forces $X$ and $Y$ to be mean-zero normal.) –  Michael Lugo Nov 6 '11 at 20:33

This is just a variation on the theme of my earlier answer. Maybe some will find this way of saying it to be clearer.

Write $(X,Y)$ in polar coordinates as $(R,\Theta)$. Their joint distribution becomes $$\text{constant}\cdot e^{-r^2/2} r\,dr\,d\theta.\tag{1}$$ From $(1)$ we see that $R$, $\Theta$ are independent and $\Theta$ is uniformly distributed in $\mathbb R\bmod 2\pi$. The ratio $N/N'$ is $\tan\Theta$. Since $\tan$ has period one-half of a circle, nothing is lost by taking $\Theta$ to be in $(-\pi/2,\pi/2)$.

$$ \frac{d}{d\theta}\Pr(\tan\Theta\le\theta) = \frac{d}{d\theta}\Pr(\Theta\le \arctan\theta) = \frac{d}{d\theta} \frac{\arctan\theta}{\pi} = \frac{1/\pi}{1+\theta^2}. $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.